Analýza vzájemného vlivu indexu vnímání míry korupce a vybraných ukazatelů v zemích Evropské unie - Koťátková-Stránská, Pavla; Linhartová, Veronika; Řízek, Zdeněk (Univerzita Pardubice, 2013)
Every country in the world is currently trying to reduce opportunities for corruption in the country. Fighting corruption is very challenging and difficult. The corruption occurs primarily in the public sector, where the object of interest is funding from public sources. Corruption has a negative impact primarily on the economy of the state in terms of their current, but also potential investors and strategic partners in the area of production. Second, it can not ignore the negative impact on the society, respectively citizens of the state affected by corruption. The paper aims to quantify the interdependence between the Corruption perception index and selected indicators of economic health in selected countries of the European Union. In terms of proven relationship between defined variables can then infer the interdependence of achieved Corruption perception index value in selected EU countries and to determine whether are these states in the problem unified or differentiated.
Analysis of mutual influence the corruption perceptions index and selected indicators in states of the European Union
Keywords: corruption; Transparency International; spearman correlation coefficient; corruption perception index